Punisher kills the Marvel Universe - Ennis, Garth; Maberry, Jonathan (Marvel Worldwide, 2024)
In a classic WHAT IF?-style tale by Frank Castle's signature writer, Garth Ennis, Frank Castle's family died not in a mob shootout, but during a superhuman slugfest. Armed with an arsenal of advanced weaponry, the Punisher seeks his revenge by hunting down Spider-Man, Magneto, Captain America, the Kingpin, Daredevil, Doctor Doom, the Hulk, Venom, Wolverine and more. One by one, group by group, the one-man army means to kill them all! Then, in another nightmarish reality, a terrible plague sweeps the Earth, turning everyone -- human, hero, villain, god and monster -- into sadistic cannibal predators. One man hunts the wasteland that was New York City, standing against the hordes of monsters who hunt the night. He is the Punisher, the Last Gun on Earth!